Asas In Dubio Pro Matrimonio dan Perlindungan Keluarga dalam Putusan Penolakan Pembatalan Perkawinan Campuran: Kajian Maqasid al-Syari‘ah dan Hukum Positif Indonesia - Dedy Supriadi; Ansari; Ramadhan Syahmedi (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2025)
This study aims to analyze the application of the principle in dubio pro matrimonio and the principle of family protection in the rejection of the annulment of a mixed marriage between an Indonesian citizen and a foreign citizen, as stated in the Religious Court Decision of Panyabungan Number 319/Pdt.G/2024/PA.Pyb. This research employs a normative juridical method with a statutory and case study approach, analyzed through the perspectives of maqasid al-shari‘ah and Indonesian positive law. The results indicate that the judge rejected the annulment request because there were no substantive grounds as stipulated in Law Number 1 of 1974 and the Compilation of Islamic Law, such as coercion, fraud, or the absence of the essential elements and requirements of marriage. Administrative deficiencies, such as the absence of an embassy permit, were deemed merely technical and did not affect the validity of the marriage contract either according to Islamic law or state law. From the maqasid al-shari‘ah perspective, this decision reflects an effort to preserve family welfare (hifz al-nasl) and protect the rights of both husband and wife. Meanwhile, the application of the in dubio pro matrimonio principle underscores the judge’s orientation toward maintaining the continuity of the household as a form of legal protection for the institution of marriage. Thus, this decision demonstrates the harmonization between the principles of substantive justice in Islamic law and the legal certainty of Indonesia’s positive law in the context of mixed marriages.